The Image of Popular Things: A Look in the Mirror (2021)
This article deals with the implications of the notion "popular" in relation to Colombian culture, taking into account the latter's specific social dynamics. The article posits that it is not pertinent to speak of high or low culture, as in Europe. What is considered as popular, as is the case with what is deemed as falling within the public sphere, nourishes a tradition that is influenced by collective expressions that are in turn affected by social violence and by certain aesthetic expressive forms. What is regarded as popular reflects our views of the world surrounding us in political, social and cultural terms. It is in this ambit that artistic proposals seeking to offer a critical context acquire their meaning.